Analisis Strategi Komunikasi Pemasaran Kopi Stralink (Kopi Keliling) di Wilayah Universitas Muhammadiyah Surakarta - Sintia Putri Agustina; Joko Sutarso (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
Along with the increasing public interest in coffee, the coffee industry in Indonesia, especially in urban areas such as Surakarta, is growing rapidly. Surakarta is one of the cultural and tourism cities that has a variety of consumer segments that are potential targets for Kopi Stralink. Starting from students, office workers, to tourists who have unique preferences that need to be accommodated in marketing strategies. This study can help Kopi Stralink management in designing a more effective marketing communication strategy. This study uses a descriptive qualitative method, which aims to describe in depth the marketing communication strategy implemented by Kopi Stralink (Kopi Keliling) in the Surakarta area. This method focuses on an in-depth understanding of the phenomena studied and relies on descriptive data. The results of the study can provide insight into the most effective communication channels and relevant approaches to be implemented so that Kopi Stralink can reach its target market more optimally in Surakarta. This study can open up discussions about social problems faced by society, especially those related to economic pressure and debt. This analysis is expected to encourage society to be more critical in understanding the impact of modern lifestyles on personal and social well-being.